Development of a Photonic Switch via Electro-Capillarity-Induced Water Penetration Across a 10-nm Gap - 유의상; Chae, Kyomin; 김태현; 이종수; Seo, Jungmok; 김인수; Chung, Aram J.; Lee, SinDoo; Ryu, YongSang (WILEY-V C H VERLAG GMBH, 2022)
With narrow and dense nanoarchitectures increasingly adopted to improve optical functionality, achieving the complete wetting of photonic devices is required when aiming at underwater molecule detection over the water-repellent optical materials. Despite continuous advances in photonic applications, real-time monitoring of nanoscale wetting transitions across nanostructures with 10-nm gaps, the distance at which photonic performance is maximized, remains a chronic hurdle when attempting to quantify the water influx and molecules therein. For this reason, the present study develops a photonic switch that transforms the wetting transition into perceivable color changes using a liquid-permeable Fabry-Perot resonator. Electro-capillary-induced Cassie-to-Wenzel transitions produce an optical memory effect in the photonic switch, as confirmed by surface-energy analysis, simulations, and an experimental demonstration. The results show that controlling the wetting behavior using the proposed photonic switch is a promising strategy for the integration of aqueous media with photonic hotspots in plasmonic nanostructures such as biochemical sensors.